A METAMODEL FOR ANALYSIS AND DESIGN OF NON-FUNCTIONAL REQUIREMENT - Liu, Yi; Ma, Zhiyi; Liu, Hui; Wei, Lai; Shao, Weizhong (Vietnam Journal of Science and Technology, 2012)
Non-Functional Requirements (NFRs) is critical for the development of user-satisfied software. Consequently, quite a few approaches have been proposed to facilitate NFRs’ analysis and design. Some of them are general, and others are NFR-specific. However, to the best of our knowledge, there is no commonly accepted taxonomy of NFRs analysis and design. Different approaches describe the same concepts or terms in different ways. This concept diversity hinders the analysis and realization of NFRs, and interferes effective communication among stakeholders. To this end, we propose a meta model to explicate the concepts relevant to NFR analysis and design, which might provide a common foundation for these tasks. In order to validate its completeness and usefulness, terms and concepts provided in this meta model are compared with the concepts appearing in the typical analysis and design approaches. Finally, a modeling tool built upon this meta model is also developed to facilitate NFR modeling and analysis.